2016
DOI: 10.18632/oncotarget.12229
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA regulatory pathway analysis identifies miR-142-5p as a negative regulator of TGF-β pathway via targeting SMAD3

Abstract: MicroRNAs (miRNAs) are non-coding RNAs with functions of posttranscriptional regulation. The abnormally expressed miRNAs have been shown to be crucial contributors and may serve as biomarkers in many diseases. However, determining the biological function of miRNAs is an ongoing challenge. By combining miRNA targets prediction, miRNA and mRNA expression profiles in TCGA cancers, and pathway data, we performed a miRNA-pathway regulation inference by Fisher's exact test for enrichment analysis. Then we constructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 45 publications
(45 reference statements)
1
39
0
Order By: Relevance
“…Previously, miR-142 displays a functional role in various cellular fuctions and disease, including cancer, virus infection, inflammation, and immune tolerance [29]. It has been reported that miR-142-5p suppresses TGF-β-induced growth inhibition by targeting SMAD3in cancer cells [30]; miR-375 and miR-142-5p regulate several oncogenic genes of TP53, MAPK and Wnt signal pathways in gastric cancer [31]; miR-142-5p inhibits cell growth and induce apoptosis by regulating FOXO in HCC [32]; miR-142-5p, targeting CLDN1, plays an important role in Hashimoto’s thyroiditis (HT) pathogenesis [33]; downregulated miR-142-5p significantly reduced cell migration and invasion in HCC [34]. In the current study, we found miR-142-5p was down-regulated in NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, miR-142 displays a functional role in various cellular fuctions and disease, including cancer, virus infection, inflammation, and immune tolerance [29]. It has been reported that miR-142-5p suppresses TGF-β-induced growth inhibition by targeting SMAD3in cancer cells [30]; miR-375 and miR-142-5p regulate several oncogenic genes of TP53, MAPK and Wnt signal pathways in gastric cancer [31]; miR-142-5p inhibits cell growth and induce apoptosis by regulating FOXO in HCC [32]; miR-142-5p, targeting CLDN1, plays an important role in Hashimoto’s thyroiditis (HT) pathogenesis [33]; downregulated miR-142-5p significantly reduced cell migration and invasion in HCC [34]. In the current study, we found miR-142-5p was down-regulated in NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, miR‐142‐5p targets Smad3 thereby suppressing TGFß‐induced growth inhibition in cancer cells. Overexpression of miR‐142‐5p leads to increased tumor cell proliferation and decreased apoptosis, while silencing of miR‐142‐5p leads to the opposite effects (Ma et al, ). Similarly miR‐142‐3p can repress TGFß‐induced growth inhibition by targeting the Tgf ß r1 receptor in nonsmall cell lung carcinoma cell lines (Lei et al, ).…”
Section: Mir‐142 In Cancermentioning
confidence: 99%
“…Liu et al pointed that miR-142-5p promoted proliferation and colony formation, but inhibited apoptosis in colorectal cancer (CRC) [9]. Ma et al reported that miR-142-5p promoted cell proliferation by attenuating TGF-β mediated inhibitory effects via targeting SMAD3 [10]. Saito et al revealed that miR-142-5p suppressed the pro-apoptotic gene TP53INP1 as its target and facilitated the pathogenesis of gastric mucosa-associated lymphoid tissue (MALT) lymphoma [11].…”
Section: Introductionmentioning
confidence: 99%